Mechanism for the dissemination of agricultural technologies in Romania - Abdulmuttaleb Abbas Salih (University of Thi-Qar Journal of agricultural research, 2021)
This research is concerned with outlining the strategies supporting the mechanisms of the dissemination of agricultural technologies in Romania. The problem in Romania in this respect is dueto a lack of a mechanism of dissemination of the agricultural technologies caused by a lack of the extension of knowledge from the units responsible for itsuch as lack of consultancy services and directions. This has affected the understanding of the importance of agricultural technologies by farmers. In an attempt to solve this problem, Romania has adopted a number of strategies for the dissemination of agricultural technologies among farmers and specialists. Among these strategies is encouraging the Management Entity of the Cluster "Sviluppo Insieme si Vince" that created IND AGRO WEST, the first innovative cluster for research and development in Romania, aimed at achievement of modern agriculture equipment, appropriate to Romanian soil (Sviluppo, 2014). Another strategy is finantially supportinginnovations and projects conducted for addressing the issue of agricultural technology dissemination through funding and financial support. For example, Climate smart agriculture is one of the key topics for the almost 3,000 innovation projects that are expected to receive funding from the Rural Development budget. Around EUR64 million will be dedicated to precision farming and digital technologies in the agriculture sector under the Horizon 2020 Work Programme for 2016-2017 while EUR30 million will be invested in the implementation of an Internet of Things Large Scale Pilot on “Smart farming and food security” (Michalopoulos, 2016). Another strategy is creating institutes that are concerned with the dissemination of agricultural technologies in Romania. The mission of the National Research and Development Institute for Machines and Installations for Agriculture and Food Industry is to carry out scientific research (fundamental and applicative), innovations in the field of processes, technologies and technical equipment leading to the mechanization and automation of agricultural works and the food industry, in the context of harmonizing the whole activity with ANCS policies. It is also important for Romania to search for collaboration with other countries such as Netherlands that runs many projects to transfer to Romanian farmers' a better understanding of technology. Dutch is another important country to collaborate with in order to transfer Dutch farmers’ knowledge to and technological novelties to Romanian young entrepreneurs. Overall,dissemination of agricultural technologies in Romania among specialists as well as farmers is essential in order to raise their awareness towards the latest knowledge and mechanisms of running agriculture. To achieve this goal, there are a number of strategies, as outlined in this research, that must be considered, with a special focus on establishing institutes for workshops and training courses, providing financial support, and collaborating with other countries. Throughout the development of mankind, a major branch of economic activity was represented by agriculture. Agricultural research has played a particularly important role in increasing production and in rational exploitation of existing resources when the population of the planet is constantly growing and the exploited agricultural fund is limited and with clear tendencies of deterioration. In this background, the mechanization of agriculture has played and continues to play a fundamental role from a technical, economic and social point of view, especially in highly industrialized countries, offering substantial cost savings, increasing the quality of works, and creating new products especially in the energy field. Romania occupies an important position in the whole of agriculture European Union, ranked 6th in the EU from the perspective of the agricultural area used, as seen in the figure below: